1990
DOI: 10.1002/hon.2900080104
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Effects of Parenteral Dichloromethylene Bisphosphonate (Cl2mbp) on Bone Disease of Myeloma Patients Treated With Chemotherapy

Abstract: Data on the long-term treatment of myeloma bone disease with bisphosphonates are scanty. In a prospective pilot trial we evaluated the effect of long-term parenteral administration of dichloromethylene bisphosphonate (Clodronate), in addition to standard chemotherapy, in 30 patients with active myeloma bone disease. Patients were treated with a mean of 4 courses (range 2-8) of Clodronate: 300 mg/day i.v. for seven days followed by 100 mg/day i.m. for 10 days, administered at a mean interval of 4 months (range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(18 citation statements)
references
References 11 publications
(12 reference statements)
0
18
0
Order By: Relevance
“…ICTP was also superior to M protein, when these markers were correlated with survival. It is known that production of the M component predicts the stage of the disease with resonable accuracy, but as a single parameter it does not predict survival (Durie & Salmon, 1975 (Elomaa et al, 1983;Merlini et al, 1990). Since the number of patients in the present study is small, we will test the validity of this conclusion in a much larger group of patients, participating in a randomised study on the effect of clodronate, combined with the ordinary treatment with melphalan and prednisolon.…”
Section: Discussionmentioning
confidence: 84%
“…ICTP was also superior to M protein, when these markers were correlated with survival. It is known that production of the M component predicts the stage of the disease with resonable accuracy, but as a single parameter it does not predict survival (Durie & Salmon, 1975 (Elomaa et al, 1983;Merlini et al, 1990). Since the number of patients in the present study is small, we will test the validity of this conclusion in a much larger group of patients, participating in a randomised study on the effect of clodronate, combined with the ordinary treatment with melphalan and prednisolon.…”
Section: Discussionmentioning
confidence: 84%
“…Although it is not recommended to manage subclinical MM with chemotherapy until overt malignancy (i.e., anemia, bone lesions on radiography) was observed, our data could change this point of view. Furthermore, some bone sparing agents such as diphosphonates could be useful in early MM since they appeared to be beneficial as long-term treatment of mouse plasmacytoma (44) and overt human MM (45,46). …”
Section: Discussionmentioning
confidence: 99%
“…In an open trial with parenteral clodronate in plasmocytoma a favorable bone response was observed as well [16], In contrast the bisphosphonate etidronate had no positive effect on bone pain, hypercalcemia, and vertebral fractures [7], In breast cancer patients with bone métastasés a beneficial effect of oral clodronate (1.6 g) could be shown in a double blind controlled trial [17]. Ir.…”
Section: Discussionmentioning
confidence: 99%